Effects of substituting wheat by rye in diets for young fattening pigs on nutrient digestibility, performance, products of intestinal fermentation, and fecal characteristics - Wilke, Volker; Kamphues, Josef (Frontiers in Veterinary Science, 2023)
Climate change and increasing demands to reduce the environmental impact of feed production are major challenges for animal nutritionists. Compared to wheat, which is commonly used in high levels in European piglet diets, rye is more efficient in using limited resources, most importantly, water and phosphorus. As a result, its cultivation has a relatively low carbon footprint. The high amounts of non-starch polysaccharides of rye might lead to an increased intestinal fermentation with potential beneficial effects on gut health. However, the high levels of non-starch polysaccharides in rye, which have a major impact on the physico-chemical conditions of the digesta, might affect digestibility and performance especially in young animals. It was therefore of interest to compare the effects of isoenergetic diets with increasing levels of rye as a replacement for wheat fed to young fattening pigs (bodyweight: 16–40 kg). The control diet contained 69% of wheat, while in the other three experimental diets, the amount of wheat was gradually replaced (by a third in each case) with rye. Thus, the experimental diets contained 23, 46, and 69% of rye. A total of 40 young pigs were housed individually in four dietary treatment groups. During a 4 week trial, effects on performance, digestibility, products of intestinal fermentation, and fecal characteristics were evaluated. There were no negative effects on feed intake and gains, even though the feed conversion ratio increased with the highest dietary rye level (69%). Digestibility rates of organic matter and crude protein did not differ significantly. Without affecting the characteristics of the feces, numerically higher amounts of intestinal fermentation products and higher colonic digesta mass were observed.